PRIORITIES OF THE PSYCHOLOGICAL EDUCATION AND TEACHER TRAINING (Scientific journal of the Fergana State University, 2023)
Use of new methods based on the most important requirements in the field of pedagogy, concentrating on  teacher’s skills.